SAAT HUKUM TIDAK BERDAYA (NASIB PEREMPUAN KORBAN KEKERASAN DALAM HIMPITAN HUKUM) - Noryamin Aini (Jurnal Kriminologi Indonesia, 2011)
The gender-based-violence is a nightmare and tragedy for women in transnational, cross cultural, geographical and civilizational boundaries. Moreover, prolonged human history has pervasively documented tragic, catastrophic facts recording women’s victimization. Culture, social system and structure, misogynic-religious interpretation, and especially patriarchal ideology have been stimulating, perpetuating and maintaining this women’s awful fate. Actually, several policies, political discretions and legal venues have been initiated and set up to be done in dealing with this issue. However, since law is just merely an epiphenomenon, a manifestation of cultural and social values, and a supra structure of economic power, the powerlessness and the paralyses of law were substantially and widely observed in this study. Hence, gender-based-victim have been dreadfully trapped within the dilemma of law.